2009
DOI: 10.3109/09638280903353422
|View full text |Cite
|
Sign up to set email alerts
|

Goal-directed functional therapy: A longitudinal study on gross motor function in children with cerebral palsy

Abstract: Gross motor function improved during GDT, and was maintained 12 weeks later. The goals were reached to a high extent, and the children gradually progressed towards their goals after the end of the intervention. The therapy did not induce any deterioration of body functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
40
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 33 publications
5
40
1
Order By: Relevance
“…The outcome of the study stresses the need of detailed process evaluation in early intervention studies, and the need of interventions that are tailored to the specific impairments of the child and the specific needs and wishes of the family. Goal directed functional therapy may offer one of the means to improve the success of early intervention (126, 127). …”
Section: Early Intervention In Cpmentioning
confidence: 99%
“…The outcome of the study stresses the need of detailed process evaluation in early intervention studies, and the need of interventions that are tailored to the specific impairments of the child and the specific needs and wishes of the family. Goal directed functional therapy may offer one of the means to improve the success of early intervention (126, 127). …”
Section: Early Intervention In Cpmentioning
confidence: 99%
“…They also work with other caregivers relating to orthotics, medication, surgery, etc [10,19]. Evidence supports strength training [20], constraint-induced therapy [21], activity-based intensive training [22], and physical activity through interactive gaming [19,23]. …”
Section: Introductionmentioning
confidence: 99%
“…2,3 Several research studies have evaluated the effects of goal-setting in physical therapy of children with cerebral palsy. [4][5][6][7][8][9] The results of a recent systematic review, however, could not provide support for the effectiveness of goal-setting within an activity-focused approach on treatment outcome. 10 The authors of this review found that none of the included studies were designed specifically to determine the effect of goal-setting per se, as goalsetting was additional to guiding the interventions.…”
Section: Introductionmentioning
confidence: 99%